Isolated limb perfusion using tumour necrosis factor α and melphalan in patients with advanced aggressive fibromatosis. Issue 13 (9th October 2014) - van Broekhoven, D L M; Deroose, J P; Bonvalot, S; Gronchi, A; Grünhagen, D J; Eggermont, A M M; Verhoef, C
Abstract: Background: Aggressive fibromatoses (desmoid tumours) may be locally aggressive, but do not metastasize. Although a conservative approach is advocated for most patients, pain and functional impairment are indications for active treatment. Tumour necrosis factor (TNF) α and melphalan-based isolated limb perfusion (TM-ILP) is a limb-saving treatment modality for soft tissue tumours. This study reports the results of TM-ILP treatment in patients with aggressive fibromatosis. Methods: Institutional databases of three European centres were searched. All patients who received TM-ILP treatment for aggressive fibromatosis between 1990 and 2012 were included. Before therapy, the patients were discussed at multidisciplinary tumour board meetings. Results: Twenty-five patients received 28 TM-ILP treatments. The median age of patients was 28 (i.q.r. 19–34) years and median hospital stay was 8 (7–12) days. Median follow-up was 84 (34–114) months. A complete response was achieved after two TM-ILP treatments, and a partial response after 17 treatments in 16 patients. Stable disease was reported after eight treatments in seven patients, including a patient with stable disease after the first treatment and progression after the second TM-ILP. Toxicity was modest after most treatments; Wieberdink grade IV (extensive epidermolysis, and threatening or manifest compartment syndrome) was seen after two TM-ILP treatments. Systemic leakage was reported after one treatment, but did not lead to systemic toxicity. Functional outcome was good; 16 patients had no physical limitations, and six patients had some limitations but did not need medical aids. Amputation was prevented in all but three patients. Conclusion: TNF-α-based ILP is effective in patients with aggressive fibromatosis. Abstract : Useful method to avoid limb impairment